PROGRAM BIMBINGAN UNTUK MEMBANTU MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Heru Sriyono (Universitas Indraprasta PGRI, 2011)
The process of teaching and learning in the school aims to enable students to achieve maximum learning outcomes, so that future students can become independent and responsible individuals. In Junior High School (SMP) Orphanage Village Putera Jakarta found students who are less independent in their learning, they prefer to reflect, does not have a study plan, not pay attention when teachers teach, not do homework (PR), and often forget about the task - a task schools that can result in low student learning outcomes. With tutoring programs are well-structured, is expected to increase independence and improve student learning conditions in schools. Tutoring program designed in the form of a fun learning atmosphere for students, so as to stimulate independent student learning. The results are obtained illustrate that the junior high school students learn independence profile Desa Putera Jakarta independent attitude of the school year 2010/2011 57.65% student learning, abilities and needs in student learning needs and goals 45.97% - 54.88% of future goals , independence and learning ability of students 58.18%, fun activities while learning 57.18%. Key words: Independence student learning, tutoring